Pembuatan Pakan Alternatif (Berbentuk pasta) Berbahan Dasar Limbah Tepung Ikan Rucah Di Desa Belubang Kabupaten Bangka Tengah: THE ALTERNATIVE FEED PRODUCTION (PASTE-FORM) WITH TRASH FISH MEAL WASTE IN BATU BELUBANG, CENTRAL BANGKA - Fitri Sil Valen; Tiara Puspa Anjani Anjani; Endang Bidayani (Buletin SWIMP, 2023)
Utilizing fish waste as alternative feed for catfish seeds has provided considerable benefits in exploiting fishery potential in maximizing "zero waste" and "Blue economy". This activity was carried out in Batu Belubang, Central Bangka on fishermen community on the coast. Currently, waste from trash fish has not been utilized properly. We started work from utilizing fish waste which were not initially utilized to become more valuable, useful and have economic value by turning the waste into the main ingredient in the manufacture of alternative feed for catfish seeds. Starting with the selection of raw materials of waste fish flour, flouring of raw materials, weighing raw materials, mixing raw materials and finally printing and experimenting with feeding catfish seeds. Every step of action was recording and then we present all of the information by sosialization. This activity was carried out to disseminate information on how to make alternative feeds and use trash fish to support aquaculture production and increase progressive income in community.